Prevalence of overweight and obesity among students of Ardabil University, Iran - Amani, Firouz; Fathi, Afshin; Farzaneh, Esmaeil; Kahnamouei-aghdam, Fariba; Goudarzian, Maryam (International Journal Of Community Medicine And Public Health, 2017)
Background: Overweight and obesity are most important health problem in all societies which its prevalence is rapidly increasing. The relationship between obesity and many diseases such as type 2 diabetes, hyperlipidemia, hypertension, coronary heart disease and breast cancer has been proven in many studies. This study aimed to determine prevalence of overweight and Obesity among 240 students of Ardabil University. Methods: As a cross sectional study height, weight, waist circumference and hip circumference were measured. Food frequency questionnaire (FFQ) was completed. BMI and WHR were used to assess the overweight and obesity. Data analyzed by statistical methods in SPSS.19. Results: Of all students, 62.5% were female and the mean age of students was 21.5±2.2. According to WHR, 66 students (27.5%) have WHR more than 0.8 (were in un-healthy range) which from them, 95.5% were female and 4.5% male. According to BMI, 123 students (51.3%) have overweight and 71 students (29.6%) obesity which from them 53.7 % and 81.7% was female, respectively. The rate of obesity and overweight was significantly in female more than male. Conclusions: According to the moderate to high prevalence of obesity and overweight between Ardabil university students, the importance of proper nutrition, improve lifestyle and providing continuing education on nutritional discussions is essential.